The psychotype of the artist in the biography novels of M. Slaboshpitskyi (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
In the articles heroes characters of М. Slaboshpytskyi biographic novels, prin-ciples of their behavior, moral and spiritual values, feelings, influenced reflections of personages, difficult heartfelt conflicts and contradictions, their tense psychological problems, causes and effects of psychical derangements are marked.
Keywords: psychtype; characters